2012
DOI: 10.1093/aje/kws267
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Smoking Bans and Acute Myocardial Infarction Among Medicare Enrollees in 387 US Counties: 1999-2008

Abstract: Restrictions on smoking in public places have become increasingly widespread in the United States, particularly since the year 2005. National-scale studies in Europe and local-scale studies in the United States have found decreases in hospital admissions for acute myocardial infarction (AMI) following smoking bans. The authors analyzed AMI admission rates for the years 1999-2008 in 387 US counties that enacted comprehensive smoking bans across 9 US states, using a study population of approximately 6 million Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 27 publications
1
50
1
2
Order By: Relevance
“…These findings complement an existing body of literature that has generally indicated that smoke-free policy implementation is associated with lower rates of hospital admissions or mortality for cardiovascular disease. 16,17,[19][20][21][22][27][28][29][30][31][32][33][34][35] Prior studies have typically been ecological in nature [14][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][34][35][36] and have not had access to detailed individual-level information on sociodemographic characteristics and cardiovascular disease risk factors. Our findings that patterns were largely similar after controlling for a large number of potential confounders suggest that differences in cardiovascular disease risk among those in areas with and without smoke-free policies are not explained by differences in individual sociodemographics or traditional cardiovascular disease risk factors.…”
Section: Original Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…These findings complement an existing body of literature that has generally indicated that smoke-free policy implementation is associated with lower rates of hospital admissions or mortality for cardiovascular disease. 16,17,[19][20][21][22][27][28][29][30][31][32][33][34][35] Prior studies have typically been ecological in nature [14][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][34][35][36] and have not had access to detailed individual-level information on sociodemographic characteristics and cardiovascular disease risk factors. Our findings that patterns were largely similar after controlling for a large number of potential confounders suggest that differences in cardiovascular disease risk among those in areas with and without smoke-free policies are not explained by differences in individual sociodemographics or traditional cardiovascular disease risk factors.…”
Section: Original Research Articlementioning
confidence: 99%
“…13 Prior studies have examined changes in hospital admissions and mortality resulting from cardiovascular events, most commonly acute myocardial infarction, from before to after smoke-free policy implementation. Results generally indicated that policies were associated with lower rates of cardiovascular admissions, although a few studies found no association, 24,25 found results to be sensitive to linearity assumptions, 14 or found associations in only certain settings 18 or subgroups of the population. 26 In addition, several prior studies have shown stronger associations of smoke-free policies with lower rates of cardiovascular disease admissions among younger age groups, [26][27][28][29] suggesting that these policies may be an effective means of reducing premature cardiovascular disease.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, as illustrated in Fig. 5, Gasparrini et al [33] in Europe and Barr et al [8] in the United States found that straight-line projections of what future heart attack (acute myocardial infarction, AMI) rates would have been in the absence of an intervention that banned smoking in public places led to a conclusion that smoking bans were associated with a significant reduction in AMI hospital admission rates following the bans. However, allowing for nonlinearity in the trend, which was significantly more consistent with the data, led to the reverse conclusion that the bans had no detectable impact on reducing AMI admission rates.…”
Section: Figmentioning
confidence: 99%
“…To this end, Shetty et al (2011) find that the relationship between smoking bans and AMI in the US is sensitive to the choice of the city and specification. For instance, using data about US-Medicare enrollees aged 66+ for the years 1999-2008, Barr et al (2012) show that the negative effect of smoking bans on AMI hospital admissions disappears as they account for non-linear adjustment for secular trend and random effects at the county level. Finally, some of these studies evaluate the effect of smoking bans in very small cities and this may lead to problems of external validity of their results (e.g.…”
Section: Introductionmentioning
confidence: 99%